HUBUNGAN MOBILISASI DINI DENGAN INVOLUSI UTERI PADA IBU NIFAS DI BPM HJ. TITIK RAHMAWATI, SST DESA LEMINGGIR KECAMATAN MOJOSARI KABUPATEN MOJOKERTO - Lestari, Indah; Umah, Khoirotul (JURNAL KEPERAWATAN SEHAT, 2016)
During childbirth, a woman still has a variety of risks, bleeding, infection or lactation problems. One important indicator is the involution process went well. The phenomenon happens, there are many mothers who delayed involution. Early mobilization as an alternative option to prevent subinvolution and acceleration of the process of involution. The purpose of this study was to analyze the relationship of early mobilization against maternal post-partum uterine involution. The research design was analytic correlation with case control approach. The research population was all puerperal women in BPM Hj. Titik Rahmawati, SST Leminggir Village Mojosari District of Mojokerto amounted to 18 respondents. Samples were 38 people taken through consecutive sampling technique. Early mobilization data collection and through direct observation of uterine involution. The Data analysis uses Chi Square. The result showed almost all respondents did early mobilization at 2-8 hours post partum as many as 35 respondents (83.3%) and the majority of respondents experienced a normal involution as many as 33 respondents (72.2%). Statistical test results obtained (ρ) = 0.013, which means there is a relationship early mobilization against maternal postpartum uterine involution in BPM Hj. Rahmawati point, SST Village Leminggir Mojosari District of Mojokerto. Early mobilization is indispensable so that the process of involution postpartum mothers either walk (TFU, Uterine Contractions, lochea), preventing thrombosis and thrombo embolism, blood circulation, prevent the occurrence of puerperal infection, uterine contractions would be good so that the risk of bleeding can be avoided.Keywords: Early mobilization, involution uteri, post-partum mother